Implementing Community Policing Model for Crime Reduction: Lessons for Pakistan (Journal of Social Sciences Review, 2023)
In recent years, the Pakistani crime rate appears to have risen considerably. In the meantime, police forces in Pakistan are incapable of successfully combating crime, upholding the law, ensuring the protection of the populace, and combating the spread of militancy. Due to the severity of the deteriorating law and order situation, the government is compelled to invest excess revenue in crime-fighting groups. Thus, there is an urgent need to deploy a new crime-control strategy known as community policing, which on the one hand, minimizes these growing crimes, increases employment prospects, and on the other hand, strengthens the community's relationship with the police. This study also investigates the efficacy of community policing in reducing crime in various countries. In addition, the necessity and challenges of building a community policing system in Pakistan are discussed. In addition, the study highlighted the obstacles to implementing community policing in Pakistan, such as police corruption and misuse of power, the presence of mistrust between the community and police, a severe lack of facilities and infrastructure, and insufficient police department transparency and openness. Community policing is the most effective strategy for controlling crime and fostering healthy connections between the community and the police in Pakistan, according to the overall findings of the study.
Keywords: Community-Oriented Policing; Crime Controlling Model; Law Enforcement Neighborhood-Oriented Policing; Police Department; Paramilitary Troops